PENGARUH KUALITAS LAYANAN DIGITAL, PROMOSI, DAN KEPERCAYAAN TERHADAP KEPUASAN PELANGGAN SHOPEEFOOD - Agus Wahyono; Aldy Ardiansyah (Jurnal Manajemen, 2021)
This study aims to determine the effect of digital services, promotions, and trust on ShopeeFood customer satisfaction at the University of Satya Negara Indonesia partially or partially. The data used is primary data collected through the distribution of questionnaires to 100 respondents who have installed the ShopeeFood application and used the ShopeeFood application. The method used in this study is a quantitative method and the research results are based on respondents' answers using a Likert scale. The data analysis method used in this research is Multiple Linear Regression Test, F Test, t Test, and Coefficient of Determination.